Pergulatan Eliti Lokal Kaharingan Dan Hindu Kaharingan Representasi Relasi Kuasa dan Identitas - Linggua Sanjaya Usop (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2016)
This essay will discuss the conflict between Kaharingan and Hindu’s Kaharingan elite in local Dayak Ngaju society about the status and identity of Kaharingan belief. Cultural Studies approach has been used to interdiciplinarily reveal the concealed root problems. Hegemony theory by Gramsci and Practice theory by Boudieu have been used as a tool of analysis: they ascertained that the Departement of Religions’ policy and construction has developed the emergence of political hegemony issues on small religions marginalization. The goverment is considered to endorse particular elite’s interests.